Spatial variability of metals in surface water and sediment in the Langat River and geochemical factors that influence their water-sediment interactions - Lim, Wan Ying; Aris, Ahmad Zaharin; Zakaria, Mohamad Pauzi (Hindawi Publishing Corporation, 2012)
This paper determines the controlling factors that influence the metals’ behavior water-sediment interaction facies and distribution of elemental content (75As, 111Cd, 59Co, 52Cr, 60Ni, and 208Pb) in water and sediment samples in order to assess the metal pollution status in the Langat River. A total of 90 water and sediment samples were collected simultaneously in triplicate at 30 sampling stations. Selected metals were analyzed using ICP-MS, and the metals’ concentration varied among stations. Metal concentrations of water ranged between 0.08–24.71 μg/L for As, <0.01–0.53 μg/L for Cd, 0.06–6.22 μg/L for Co, 0.32–4.67 μg/L for Cr, 0.80–24.72 μg/L for Ni, and <0.005–6.99 μg/L for Pb. Meanwhile, for sediment, it ranged between 4.47–30.04 mg/kg for As, 0.02–0.18 mg/kg for Cd, 0.87–4.66 mg/kg for Co, 4.31–29.04 mg/kg for Cr, 2.33–8.25 mg/kg for Ni and 5.57–55.71 mg/kg for Pb. The average concentration of studied metals in the water was lower than the Malaysian National Standard for Drinking Water Quality proposed by the Ministry of Health. The average concentration for As in sediment was exceeding ISQG standards as proposed by the Canadian Sediment Quality Guidelines. Statistical analyses revealed that certain metals (As, Co, Ni, and Pb) were generally influenced by pH and conductivity. These results are important when making crucial decisions in determining potential hazardous levels of these metals toward humans.